Artificial formate oxidase reactivity with nano-palladium embedded in intrinsically microporous polyamine (Pd@PIM-EA-TB) driving the H2O2 – 3,5,3′,5′-tetramethylbenzidine (TMB) colour reaction - Mariolino Carta (Journal of Catalysis, 2022)
Surface cavities formed by molecularly rigid polymers of intrinsic microporosity affect catalytic processes. Palladium nanoparticles of typically 3 nm diameter are formed in an intrinsically microporous polyamine (PIM-EA-TB) by borohydride reduction. These particles are shown to indirectly catalyse the oxidative colour change of indicator dye 3,5,3′,5′-tetramethylbenzidine (TMB) in the presence of formic acid via formation of H2O2. Investigation reveals that oxygen reduction on the palladium is rate limiting with optimised H2O2 production at approximately pH 3 to 4, and first order in formate, followed by purely homogeneous TMB oxidation. The H2O2 production is therefore studied separately as a nanozyme-like catalytic process equivalent to formate oxidase reactivity, linked to the molecularly rigid polyamine host (PIM-EA-TB) providing ammonium sites (in molecularly rigid surface cavities) that enhance both (i) 2-electron formate oxidation and (ii) 2-electron oxygen reduction to H2O2. Beneficial effects of hydrophobic ClO4- anions are noted as indirect evidence for the effect of ammonium sites in surface cavities. A computational DFT model for the artificial formate oxidase reactivity is developed to underpin and illustrate the hypothesis of PIM-EA-TB as an active catalyst component with implications for future nanozyme sensor development.